Human health risks of metal contamination in Shallow Wells around waste dumpsites in Abeokuta Metropolis, Southwestern, Nigeria - Okoye, Harvester O.; Bankole, Abayomi O. [UNESP]; Ayegbokiki, Adedayo O.; James, Abraham O. [UNESP]; Bankole, Afolashade R. [UNESP]; Oluyege, Damilola E. (Springer Nature, 2023)
Metal contamination in shallow wells through solid waste leaching is a serious environmental problem with contribution to global cancer cases. This paper evaluated the health risks of metals in shallow wells around dumpsites in the Abeokuta metropolis, Nigeria. Five dumpsites were purposively selected to sample twenty-five shallow wells. In situ and laboratory analyses for physico-chemical parameters, copper, lead, cadmium, iron, and chromium were conducted following the APHA standard procedure. Carcinogenic and non-carcinogenic risks for oral and dermal routes were evaluated for adult males and females, children, and infants. Findings revealed that all wells were acidic (pH = 5.82–6.48), with Fe and Cd concentrations above the established limits. The wells around Obada, Obantoko, and Saje dumpsites had high EC (up to 1200 µS/cm), Cu, and Pb concentrations above the permissible limits. Non-carcinogenic risks for oral ingestion were significant for all age groups (hazard index: HI > 1), and the significance level across dumping areas increased in the order: Saje > Obantoko > Obada > Idi-aba > Lafenwa. All wells assessed in Saje and Obantoko recorded significant HI of dermal exposure for children and infants. Cancer risks were significant for all age groups (CR > 1.0E − 04), and metal contributions followed: Cd > Cr > Pb. The overall trend of significant risks for non-carcinogenic and carcinogenic via oral and dermal routes is in the order of infant > children > adult female > adult male. This suggests that groundwater users within the studied areas may experience diverse illnesses or cancer in their lifetime, particularly children and infants. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Abeokuta metropolis; Dumpsites; Health risks; Leachates; Metal contamination; Shallow well